Differential trypanosome surface coat regulation by a CCCH protein that co-associates with procyclin mRNA cis-elements. - Pegine Walrad; Athina Paterou; Alvaro Acosta-Serrano; Keith R Matthews (PLoS Pathogens)
The genome of Trypanosoma brucei is unusual in being regulated almost entirely at the post-transcriptional level. In terms of regulation, the best-studied genes are procyclins, which encode a family of major surface GPI-anchored glycoproteins (EP1, EP2, EP3, GPEET) that show differential expression in the parasite's tsetse-fly vector. Although procyclin mRNA cis-regulatory sequences have provided the paradigm for post-transcriptional control in kinetoplastid parasites, trans-acting regulators of procyclin mRNAs are unidentified, despite intensive effort over 15 years. Here we identify the developmental regulator, TbZFP3, a CCCH-class predicted RNA binding protein, as an isoform-specific regulator of Procyclin surface coat expression in trypanosomes. We demonstrate (i) that endogenous TbZFP3 shows sequence-specific co-precipitation of EP1 and GPEET, but not EP2 and EP3, procyclin mRNA isoforms, (ii) that ectopic overexpression of TbZFP3 does not perturb the mRNA abundance of procyclin transcripts, but rather that (iii) their protein expression is regulated in an isoform-specific manner, as evidenced by mass spectrometric analysis of the Procyclin expression signature in the transgenic cell lines. The TbZFP3 mRNA-protein complex (TbZFP3mRNP) is identified as a trans-regulator of differential surface protein expression in trypanosomes. Moreover, its sequence-specific interactions with procyclin mRNAs are compatible with long-established predictions for Procyclin regulation. Combined with the known association of TbZFP3 with the translational apparatus, this study provides a long-sought missing link between surface protein cis-regulatory signals and the gene expression machinery in trypanosomes.